Pemahaman Konsep Minyak Bumi Hasil Pembelajaran Menggunakan Model Kooperatif Tipe SQ3R Di SMA Negeri 4 Palangka Raya Tahun Ajaran 2017∕2018 - Anjeli Anjeli; Ruli Meiliawati; Abdul Hadjranul Fatah (Jurnal Ilmiah Kanderang Tingang, 2020)
The purpose of this study is to describe students' understanding of the concept of petroleum learning outcomes using the SQ3R type of cooperative learning model (Survey-Question-Read-Recite-Review) in Public Senior High School 4 Palangka Raya in the Academic Year 2017/2018. This study involved 24 students. The instrument used was a concept understanding test in the form of an essay given during pretest and posttest, management of learning management and student questionnaire responses. Data on students' understanding of concepts were obtained from written test results in the form of essays given before and after learning using the SQ3R cooperative learning model. The results showed the average understanding of the concepts of class XI students was 84.3%. The students' understanding of each concept was as follows: (i) most students (84.3%) can explain the theory of the formation of petroleum according to Duplex theory. (ii) Most students (89.1%) can explain the main components of petroleum. (iii) Most students (78.9%) can explain the results of the petroleum fraction that has C11-C14 atoms and their uses. (iv) Most students (82.2%) can explain the results of the petroleum fraction with the lowest boiling point and its uses. (v) Most students (88.6%) can explain the quality of gasoline based on octane numbers. The steps of the SQ3R learning model that most play a role in improving students' understanding of concepts are in the Question, Read and Recite activities.